Guernsey : Financial Sector Assessment Program Update-Detailed Assessment of Observance on Basel Core Principles. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Basel Core Principles for Effective Banking Supervision (BCP) assessment confirms the high standard of prudential regulation and supervision described in the 2003 assessment, and found that the issues identified have largely been addressed. The Guernsey Financial Services Commission (GFSC), being the integrated regulator, is responsible for the regulation and supervision of all financial institutions and services provided on the island, and as the banking supervisor, has disciplinary powers to address safety and soundness issues. The GFSC cooperates with the home supervisors of institutions active on the island. Several broad areas for further action have been identified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet